1991
DOI: 10.1021/jm00105a045
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-independent phosphodiesterase inhibitors as putative antidepressants: [3-(bicycloalkyloxy)-4-methoxyphenyl-2-imidazolidinones

Abstract: The synthesis and biological properties of a novel series of selective calcium-independent phosphodiesterase inhibitors are described. These compounds also inhibit the specific binding of [3H]rolipram to rat brain membranes and exhibit efficacy in preclinical models of antidepressant activity in mice, such as reducing immobility in the forced-swim test and reversing reserpine-induced hypothermia. Imidazolidinones 4 and 16 were found to be the most potent compounds studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…It has been reported that the PDE4 inhibitor CP 76,593, even though more potent than rolipram for the inhibition of high-affinity [ 3 H]rolipram binding, is considerably less potent than rolipram for producing antidepressant-like effects on differential reinforcement of low response rate (DRL) behavior (O'Donnell, 1993). In addition, the potency order of a series of drugs for inhibition of high- (Saccomano et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the PDE4 inhibitor CP 76,593, even though more potent than rolipram for the inhibition of high-affinity [ 3 H]rolipram binding, is considerably less potent than rolipram for producing antidepressant-like effects on differential reinforcement of low response rate (DRL) behavior (O'Donnell, 1993). In addition, the potency order of a series of drugs for inhibition of high- (Saccomano et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…8 PDE4 hydrolyzes cyclic AMP formed by stimulation of beta adrenergic receptor-linked adenylyl cyclase in brain cortical slices. 9 Rolipram or other selective inhibitors of PDE4 have antidepressant activity in both preclinical 10 and clinical tests 11 and produces memory-enhancing effects in animal models. 12,13 Repeated treatment of animals with SNRIs may up-regulate PDE4.…”
Section: Introductionmentioning
confidence: 99%
“…This has been confirmed using [ 3 H]-3-(cyclopentyloxy)-N-(3,5-dichloropyridin-4-yl)-4-methoxybenzamide (piclamilast), which binds with equal high affinity to the HARBS and LARBS (Zhao et al, 2003a). Although the LARBS is found in both the brain and peripheral tissues, the HARBS is found only in the brain; consistent with this, the HARBS and LARBS mediate distinct pharmacological effects (Saccomano et al, 1991;Barnette et al, 1996;Zhao et al, 2003b).…”
Section: Introductionmentioning
confidence: 61%